Males That Silence Their Father's Genes: Genomic Imprinting of a Complete Haploid Genome. (4th March 2021) - de la Filia, Andrés G; Mongue, Andrew J; Dorrens, Jennifer; Lemon, Hannah; Laetsch, Dominik R; Ross, Laura
Abstract: Genetic conflict is considered a key driver in the evolution of reproductive systems with non-Mendelian inheritance, where parents do not contribute equally to the genetic makeup of their offspring. One of the most extraordinary examples of non-Mendelian inheritance is paternal genome elimination (PGE), a form of haplodiploidy which has evolved repeatedly across arthropods. Under PGE, males are diploid but only transmit maternally inherited chromosomes, while the paternally inherited homologues are excluded from sperm. This asymmetric inheritance is thought to have evolved through an evolutionary arms race between the paternal and maternal genomes over transmission to future generations. In several PGE clades, such as the mealybugs (Hemiptera: Pseudococcidae), paternal chromosomes are not only eliminated from sperm, but also heterochromatinized early in development and thought to remain inactive, which could result from genetic conflict between parental genomes. Here, we present a parent-of-origin allele-specific transcriptome analysis in male mealybugs showing that expression is globally biased toward the maternal genome. However, up to 70% of somatically expressed genes are to some degree paternally expressed, while paternal genome expression is much more restricted in the male reproductive tract, with only 20% of genes showing paternal contribution. We also show that parent-of-origin-specific gene expression patterns are remarkably similar across genotypes, and that genes with completely biparental expression show elevated rates of molecular evolution. Our results provide the clearest example yet of genome-wide genomic imprinting in insects and enhance our understanding of PGE, which will aid future empirical tests of evolutionary theory regarding the origin of this unusual reproductive strategy.